Analysis of Thermal-structural Coupling Characteristic of Friction Pair of Single Cone Ring Synchronizer - Jingyue Huang; Zhigang Zhang; Caihong Peng; Shaokun Du (Jixie chuandong)
In order to study the influence of working conditions and structural parameters on the temperature and stress fields of the friction pair of the single cone ring synchronizer，the finite element analysis model of the thermal structure is established by Abaqus software in combination with the actual structure and working conditions of the synchronizer，and the temperature and stress fields in the shift process of synchronizer are analyzed by using the direct coupling method and the control variable method. The results show that，the temperature and stress increase with the increase of the speed difference，the sliding time and the direct pressure，and increasing direct pressure has a significant effect on it. The decrease of initial temperature does not change the temperature rise in the process of synchronous shifting，but the stress of the ring decreases significantly. The decrease of the cone angle of the friction reduces the temperature and stress，while the decrease of the inner diameter of the ring increases the temperature and stress under the same conditions. The temperature of the friction pair decreases along the axial and radial direction，and distributes uniformly along the circumferential direction.